2002
DOI: 10.1034/j.1399-6576.2003.470103.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose bupivacaine plus fentanyl for spinal anesthesia during ambulatory inguinal herniorrhaphy: a comparison between 6 mg and 7. 5 mg of bupivacaine

Abstract: Spinal anesthesia with bupivacaine 7.5 mg and fentanyl offers an alternative to general or local anesthesia for ambulatory inguinal herniorrhaphy. However, the long discharge times and risk for urinary retention restrict its routine use in all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
3
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(75 citation statements)
references
References 26 publications
8
63
3
1
Order By: Relevance
“…This finding is comparable to the studies done by Singh et al and Ben David et al 9,12 Thus, it is evidenced that intrathecal Fentanyl was not involved in the incidence of bradycardia. Similarly, there was no respiratory depression, excessive sedation or drowsiness observed in both the groups that was in accordance with the studies of Gupta et al, Singh et al, Ben David et al and Belzarena et al 7,12,9,16 In our study, shivering occurred in 36% of group B and only 8% of group BF patients. Similar significant findings were reported by Biswas et al and Techanivate et al 21,22 This is due to added Fentanyl to the Bupivacaine.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This finding is comparable to the studies done by Singh et al and Ben David et al 9,12 Thus, it is evidenced that intrathecal Fentanyl was not involved in the incidence of bradycardia. Similarly, there was no respiratory depression, excessive sedation or drowsiness observed in both the groups that was in accordance with the studies of Gupta et al, Singh et al, Ben David et al and Belzarena et al 7,12,9,16 In our study, shivering occurred in 36% of group B and only 8% of group BF patients. Similar significant findings were reported by Biswas et al and Techanivate et al 21,22 This is due to added Fentanyl to the Bupivacaine.…”
Section: Discussionsupporting
confidence: 81%
“…Intrathecal Fentanyl has already shown to prolong the duration of local anaesthetic blockade in dose dependent manner. 5,[14][15][16] A combination of Bupivacaine 7.5 mg + Fentanyl 25 µg as a spinal anaesthesia proved to be safe and effective in relieving the intense pain associated with inguinal herniorrhaphy by the studies conducted by Gupta et al, H Singh et al, Song et al 7,9,17 Kuusniemi et al, also evaluated the effect of addition of 25 µg Fentanyl to various doses of Bupivacaine (10, 7.5, 5 mg) in urological surgeries, and found increase in the intensity and duration of sensory block by Fentanyl. 18 In our study, the earlier onset of surgical anaesthesia and peak sensory level in Group B may be because of cephalad spread of spinal blockade.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] In 41 studies (5,548 patients), urinary retention or PVR with intrathecal anesthesia was assessed (Table 3), 11,13,16,17,20,22, and in 39 studies (4,938 patients), urinary retention or PVR with epidural anesthesia and/or analgesia was assessed (Table 4). 28,33,35,43,[48][49][50]54, An additional five studies involved both intrathecal and epidural techniques.…”
Section: Resultsmentioning
confidence: 99%
“…45,64 In contrast, studies in which either intrathecal fentanyl or sufentanil was utilized reported lower incidence rates ranging from 0 to 25%. 12,16,18,46,48,57,61 Kamphuis et al…”
Section: Resultsmentioning
confidence: 99%